2022
DOI: 10.3390/biology11121786
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable and Predictive Deep Neural Network Modeling of the SARS-CoV-2 Spike Protein Sequence to Predict COVID-19 Disease Severity

Abstract: Through the COVID-19 pandemic, SARS-CoV-2 has gained and lost multiple mutations in novel or unexpected combinations. Predicting how complex mutations affect COVID-19 disease severity is critical in planning public health responses as the virus continues to evolve. This paper presents a novel computational framework to complement conventional lineage classification and applies it to predict the severe disease potential of viral genetic variation. The transformer-based neural network model architecture has addi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Instead, the most recent approaches to biomedical text extraction tasks have employed transformer-based techniques, as reviewed in [ 36 ] and [ 37–39 ]; they report that current works are mainly focused on connections between entities [ 40 , 41 ]. Very few works addressed results’ explainability combined with transformers in this domain [ 42 , 43 ].…”
Section: Related Workmentioning
confidence: 99%
“…Instead, the most recent approaches to biomedical text extraction tasks have employed transformer-based techniques, as reviewed in [ 36 ] and [ 37–39 ]; they report that current works are mainly focused on connections between entities [ 40 , 41 ]. Very few works addressed results’ explainability combined with transformers in this domain [ 42 , 43 ].…”
Section: Related Workmentioning
confidence: 99%
“…Machine learning models have been successfully applied to complex phenomena, including cardiovascular diseases [ 26 ], and to make reliable predictions for emerging COVID-19 variants. For instance, as in [ 27 ], where the authors introduced a novel interpretable deep learning architecture to predict SARS-Cov-2 disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…First, there is a dire need for improved surveillance of viral evolution. Predictive tools linking viral sequence to immune evasion potential are critical at this point, and a number of groups have demonstrated that such approaches are indeed technically feasible [86][87][88][89][90][91][92] . These methods should be deployed at scale-global monitoring of viral evolution and accurate threat forecasting are critical for preventing a sudden mortality event.…”
mentioning
confidence: 99%